Sustainable Tourism in Svalbard: Balancing economic growth, sustainability, and environmental governance. (29th November 2021) - Hovelsrud, Grete K.; Veland, Siri; Kaltenborn, Bjørn; Olsen, Julia; Dannevig, Halvor
Abstract: This commentary introduces a methodology and theoretical framework for studying how the tourism industry might balance the competing demands of economic growth and environmental governance. We focus on the "balancing act" Svalbard tourism industry must play among sometimes competing demands of climate change mitigation and emissions from tourism, and of strict Norwegian environmental management policy and demands for increased tourism. While these are specific to Svalbard, the balancing act of competing needs is the core challenge of the UN Sustainability Goals giving this research global and pan-Arctic relevance. Through collaboration between two tourism organisations, the Association of Arctic Expedition Cruise Operators (AECO) and Visit Svalbard and an interdisciplinary team of scientists, we will co-produce knowledge about how to innovate new opportunities while protecting the wilderness, the very backbone of tourism. This collaboration considers how policy, climate change, and local attitudes together may affect the tourism industry and helps to define and develop sustainable tourism operations and products. For instance, tourists may participate in environmental and community-related activities or "micro safaris" rather than a sole focus on charismatic megafauna. Policy discussions about tourism growth need to consider how local and national governments anticipate and navigate rapid social, political, and environmental changes.